Effects of leptin deficiency on postnatal lung development in mice - Huang, Kewu (American Physiological Society, 2008)
Leptin modulates energy metabolism and lung development. We hypothesize that the effects of leptin on postnatal lung development are volume dependent from 2 to 10 wk of age and are independent of hypometabolism associated with leptin deficiency. To test the hypotheses, effects of leptin deficiency on lung maturation were characterized in age groups of C57BL/6J mice with varying Lep(ob) genotypes. Quasi-static pressure-volume curves and respiratory impedance measurements were performed to profile differences in respiratory system mechanics. Morphometric analysis was conducted to estimate alveolar size and number. Oxygen consumption was measured to assess metabolic rate. Lung volume at 40-cmH(2)O airway pressure (V(40)) increased with age in each genotypic group, and V(40) was significantly (P < 0.05) lower in leptin-deficient (ob/ob) mice beginning at 2 wk. Differences were amplified through 7 wk of age relative to wild-type (+/+) mice. Morphometric analysis showed that alveolar surface area was lower in ob/ob compared with +/+ and heterozygote (ob/+) mice beginning at 2 wk. Unlike the other genotypic groups, alveolar size did not increase with age in ob/ob mice. In another experiment, ob/ob at 4 wk received leptin replacement (5 μg·g(−1)·day(−1)) for 8 days, and expression levels of the Col1a1, Col3a1, Col6a3, Mmp2, Tieg1, and Stat1 genes were significantly increased concomitantly with elevated V(40). Leptin-induced increases in V(40) corresponded with enlarged alveolar size and surface area. Gene expression suggested a remodeling event of lung parenchyma after exogenous leptin replacement. These data support the hypothesis that leptin is critical to postnatal lung remodeling, particularly related to increased V(40) and enlarged alveolar surface area.